Left over: Methods to make use of the unused - Hedner, Olof (My University, 2024)
In an extractive building sector marked by substantial turnovers, recent supply disruptions have exposed the fragility of long-term material planning. Tiny delays can cause seismic effects in a reality where just-in-time orders are key for meeting deadlines. Dealing with leftover building materials due to safety margins is a common dilemma in the construction industry, and the lack of regulations in Sweden has created an informal but small market of reselling. However, this alternative turns out insufficient for big actors where irregular quantities, processing time, and unprofitable returns make leftover trade into a mostly avoided concern. This thesis develops a method where common leftover building materials are used outside of their conformity. Referencing Charles Jencks’ and Nathan Silver’s notion of Adhocism, the research employs urgency and purpose through assemblage design. Research on current reuse practices are conducted to create a systematic view, including Rotor DC in Brussels and the Swedish initiative CCBuilds. Much like Martino Gamper’s project 100 chairs in 100 days, the method strives to map and use what is discarded and readily available instead of searching for perfect parts. Departing from an assemblage case study of 400 leftover roof tiles, a site has been selected in the rural municipality of Sotenäs, north of Gothenburg. At the former granite quarry Udden in Hunnebostrand there is currently a discussion to establish Stenens Hus, a national centre for stone industry and art. Sotenäs, a municipality with a relatively large building stock compared with its population, acts as a sourcing ground for materials in quantities approximated from annual municipal leftover rates. The proposal suggests how Stenens Hus could be assembled using such leftover material, including discarded granite quarried at Udden. The research design employs mixed methods, combining quantitative and qualitative approaches in four stages: inventory, translation, embodiment and implement. The outcome suggests systemic ways in which leftover materials could be organized in a rural Swedish context as well as speculative ways to combine various building materials outside of their intended use.
Keywords: Adhocism, Assemblage, Reuse